2017
DOI: 10.1111/acel.12642
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 negatively regulates spatial memory in a mouse model of Alzheimer's disease

Abstract: SummaryThe accumulation and deposition of beta‐amyloid (Aβ) is a key neuropathological hallmark of Alzheimer's disease (AD). Histone deacetylases (HDACs) are promising therapeutic targets for the treatment of AD, while the specific HDAC isoforms associated with cognitive improvement are poorly understood. In this study, we investigate the role of HDAC3 in the pathogenesis of AD. Nuclear HDAC3 is significantly increased in the hippocampus of 6‐ and 9‐month‐old APPswe/PS1dE9 (APP/PS1) mice compared with that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 42 publications
5
74
4
Order By: Relevance
“…Unlike other Class I HDACs, HDAC3 contains both nuclear export signal (180-313 aa in the central portion) and the nuclear localization signal (312-428 aa in the C-terminal), 22 which indicated that HDAC3 may shuttle between the cytoplasm and nucleus by itself. In neurological diseases, the critical roles of HDAC3 in Huntington disease 1 and Alzheimer disease [26][27][28] have been well established. Emerging evidences suggested that cytoplasmic translocation of HDAC3 may be related with inflammatory molecular including IκBα 23 and STAT3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other Class I HDACs, HDAC3 contains both nuclear export signal (180-313 aa in the central portion) and the nuclear localization signal (312-428 aa in the C-terminal), 22 which indicated that HDAC3 may shuttle between the cytoplasm and nucleus by itself. In neurological diseases, the critical roles of HDAC3 in Huntington disease 1 and Alzheimer disease [26][27][28] have been well established. Emerging evidences suggested that cytoplasmic translocation of HDAC3 may be related with inflammatory molecular including IκBα 23 and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…25 Thus, accurately understanding the biological effects of specific HDACs could be beneficial to the development of more specific and well-tolerated therapeutic strategies. In neurological diseases, the critical roles of HDAC3 in Huntington disease 1 and Alzheimer disease [26][27][28] have been well established. HDAC3 was reported to participate in dopaminergic neuronal cell death 29 and embryonic neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modulations commonly occur at histones, remodeling chromatin between relatively 'open' and 'closed' forms (10). Significant decreased acetylation of histone was reported in both AD transgenic mice and postmortem human brains (11). The level of histone acetylation is regulated by acetyltransferase and histone deacetylase (HDAC).…”
Section: Introductionmentioning
confidence: 99%
“…An increase of HDAC2 was observed in the hippocampus of AD patients (12). The electrostatic interaction between positively charged histones and negatively charged DNA leads to a condensed and repressive chromatin structure (10,11). The acetylation of histones attenuates their positive charges, resulting in a reduced affinity of histones to DNA and a free chromatin for recruiting transcription factors to genes (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation